SOCIAL MEDIA AND LOCAL WISDOM: ETHICAL COMMUNICATION MODEL FOR CONTENT CREATORS BUGIS-MAKASSAR - Hamson, Zulkarnain; Akbar, Muhammad; Aziz, Syamsuddin (Yayasan Education and Social Center, 2025)
Social media has become a primary space for content creators to express ideas, share information, and build communities. However, digital communication practices often ignore local wisdom values amid globalization. This study aims to develop a communication ethics model for content creators with an approach to Bugis-Makassar's local wisdom values. Values ​​such as